Effects of Curcumin on Hematological Parameters in Aflatoxin B1 Applied Rats - Deniz Uluışık; Ercan Keskin; Durmuş Hatipoğlu (Türk Spor ve Egzersiz Dergisi)
In this study, it is aimed to determine the possible effects of curcumin on hematological parameters in aflatoxin applied rats. Thirty eight healthy male Wistar Albino rats were used in the study. Group I animals was no applied. Animals in Group II were orally given 1 ml 10% DMSO daily for 60 days. Animals in Group III were orally given 300 mg/kg curcumin dissolved in 10% DMSO daily for 60 days. Animals in Group IV were orally given 250 µg/kg aflatoxin B1 dissolved in 10% DMSO daily for 60 days. Animals in Group V was orally given 250 µg/kg aflatoxin B1 dissolved in 10% DMSO and 300 mg/kg curcumin dissolved in 10% DMSO daily for 60 days. At the end of the study, erythrocyte count, leukocyte count, platelet count, hemoglobin amount, hematocrit value, percentage ratios of leukocyte types, mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC) were determined in blood samples taken from all animals. In the study, erythrocytes count, hemoglobin concentration, hematocrit value and MCHC level in the aflatoxin applied rats significantly decreased compared to the control group (p